Предмет: Алгебра,
автор: VIKA4583
a)(c^2)^4*c^5c^12
б)(x-3)(x-7)-(x-2)(x+2)
в)(3а+4)^2-24a
Ответы
Автор ответа:
0
а). (с^ 2*4) * (c ^ 5-12) = c^8 * c ^-7 = c ^ 8+(-7) = c
б). x^2 - 7x - 3x + 21 - x^2 +4 = -7x-3x+21 +4 = -10x +25
-10x=-25
x=-25/-10
x= 2,5
в). 9a^2 + 24a + 16 -24a = 9a^2 + 16
9a^2 = -16
a^2 = -16/9
a = -4/3
б). x^2 - 7x - 3x + 21 - x^2 +4 = -7x-3x+21 +4 = -10x +25
-10x=-25
x=-25/-10
x= 2,5
в). 9a^2 + 24a + 16 -24a = 9a^2 + 16
9a^2 = -16
a^2 = -16/9
a = -4/3
Похожие вопросы
Предмет: Алгебра,
автор: kirillsergeev041
Предмет: Обществознание,
автор: drogol
Предмет: Математика,
автор: hristomorozov
Предмет: Математика,
автор: heba1
Предмет: Алгебра,
автор: lexa9814